2009
DOI: 10.1111/j.1440-1681.2009.05348.x
|View full text |Cite
|
Sign up to set email alerts
|

Rna Interference-Mediated Silencing of Ubch10 Gene Inhibits Colorectal Cancer Cell Growth in Vitro and in Vivo

Abstract: 1. UbcH10 is the cancer-related E2 ubiquitin-conjugating enzyme, and its overexpression has been demonstrated in a variety of malignancies. The aim of the present study is to silence UbcH10 gene by RNA interference (RNAi) and to observe its inhibitory effect on the colorectal cancer cell growth in vitro and in vivo. 2. We constructed the expression vector pGPU6/GFP/Neo/UbcH10-RNAi (pUbcH10-RNAi), which contained a UbcH10 short hairpin RNA expression cassette. Then the UbcH10 gene silencing cell lines LoVo/UbcH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…This confirmed that the expression of UbcH10 is correlated with the proliferation activity of cancer cells. In accordance with the results of the present study, a previous study demonstrated that a knockdown of UbcH10 inhibited the cellular proliferation of other cancer cells, including those of lung, glioma and colorectal cancers (13)(14)(15). It is therefore hypothesized that OS cell growth inhibition is caused by UbcH10-mediated cell cycle regulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This confirmed that the expression of UbcH10 is correlated with the proliferation activity of cancer cells. In accordance with the results of the present study, a previous study demonstrated that a knockdown of UbcH10 inhibited the cellular proliferation of other cancer cells, including those of lung, glioma and colorectal cancers (13)(14)(15). It is therefore hypothesized that OS cell growth inhibition is caused by UbcH10-mediated cell cycle regulation.…”
Section: Discussionsupporting
confidence: 78%
“…An overexpression of UbcH10 is significantly associated with the pathological grading of tumors, high cellular proliferation and poor prognoses of cancers affecting the adrenal gland, breast, colon, liver, lung and ovary (10,11). Furthermore, UbcH10 transgenic mice are prone to developing a range of spontaneous and carcinogen-induced tumors (12 (13,14). However, limited evidence exists regarding the biological function of UbcH10 in OS.…”
Section: Introductionmentioning
confidence: 99%
“…Using these cells, we demonstrated that the inhibition of UbcH10 potently retarded the proliferation of tumor cells. Chen et al obtained similar results via RNA interference-mediated silencing of UbcH1022. Importantly, cell cycle changes and the accumulation of cyclin A and cyclin B1 were directly tested in endogenous conditions.…”
Section: Discussionmentioning
confidence: 80%
“…All the recombinant plasmids were confirmed by DNA sequencing. The MKN-45 cells were transfected with pGPU6/GFP/Neo-CREG siRNAs, and/or control siRNA using Lipofectamine TM 2000 reagent (Invitrogen), and were selected with G418 at the concentration of 500 lg/ml [9]. Subsequently, the knockdown efficiency was assessed via real-time RT-PCR and Western-blot analysis.…”
Section: Rna Interferencementioning
confidence: 99%